Comparing the immunomodulatory properties of equine BM-MSCs culture expanded in autologous platelet lysate, pooled platelet lysate, equine serum and fetal bovine serum supplemented culture media - Even, Kayla M.; Gaesser, Angela M.; Ciamillo, Sarah A.; Linardi, Renata L.; Ortved, Kyla F. (Frontiers in Veterinary Science, 2022)
Joint injury often leads to cartilage damage and posttraumatic inflammation, which drives continued extracellular matrix degradation culminating in osteoarthritis. Mesenchymal stem cells (MSCs) have been proposed as a biotherapeutic to modulate inflammation within the joint. However, concerns have been raised regarding the immunogenicity of MSCs cultured in traditional fetal bovine serum (FBS) containing media, and the potential of xenogenic antigens to activate the immune system causing rejection and destruction of the MSCs. Xenogen-free alternatives to FBS have been proposed to decrease MSC immunogenicity, including platelet lysate (PL) and equine serum. The objective of this study was to compare the immunomodulatory properties of BM-MSCs culture-expanded in media supplemented with autologous PL (APL), pooled PL (PPL), equine serum (ES) or FBS. We hypothesized that BM-MSCs culture expanded in media with xenogen-free supplements would exhibit superior immunomodulatory properties to those cultured in FBS containing media. Bone marrow-derived MSCs (BM-MSCs) were isolated from six horses and culture expanded in each media type. Blood was collected from each horse to isolate platelet lysate. The immunomodulatory function of the BM-MSCs was assessed via a T cell proliferation assay and through multiplex immunoassay quantification of cytokines, including IL-1β, IL-6, IL-8, IL-10, and TNFα, following preconditioning of BM-MSCs with IL-1β. The concentration of platelet-derived growth factor BB (PDGF-BB), IL-10, and transforming growth factor-β (TGF-β) in each media was measured via immunoassay. BM-MSCs cultured in ES resulted in significant suppression of T cell proliferation (p = 0.02). Cell culture supernatant from preconditioned BM-MSCs cultured in ES had significantly higher levels of IL-6. PDGF-BB was significantly higher in APL media compared to FBS media (p = 0.016), while IL-10 was significantly higher in PPL media than ES and FBS (p = 0.04). TGF-β was highest in APL media, with a significant difference in comparison to ES media (p = 0.03). In conclusion, expansion of equine BM-MSCs in ES may enhance their immunomodulatory abilities, while PL containing media may have some inherent therapeutic potential associated with higher concentrations of growth factors. Further studies are needed to elucidate which xenogen-free supplement optimizes BM-MSC performance.